Impact of supportive periodontal therapy and implant surface roughness on implant outcome in patients with a history of periodontitis - Marc Quirynen (Blackwell Synergy, 2007)
Objective: This review searched for a relationship between susceptibility to periodontitis and peri-implantitis, with implant outcome as the primary outcome variable and supportive periodontal therapy (SPT) and implant surface roughness as confounding factors. Material and Methods: It is based on a MEDLINE search up to June 2006. Only 16 fulfilled the selection criteria. The heterogeneity of the studies (e.g. periodontal status, SPT, prosthetic design, . . .) rendered a meta-analysis impossible. The impact of a history of periodontitis on early implant loss was negligible. Only five papers reported sub-data for patients with different degrees of periodontitis. Four out of five papers indicate a higher incidence of late implant loss and/or marginal bone loss in patients with a history of periodontitis. This difference was most obvious for very rough implants (three papers), and/or when SPT was not organized (one paper). Other confounding factors were often neglected. Another 10 papers only reported the outcome of implants in patients with a history of periodontitis. In case of SPT and when avoiding roughened surfaces, late implant loss remained below 3%, and marginal bone loss remained low. Conclusions: These results seem to indicate that periodontally compromised patients can be successfully treated with minimally/moderately rough implants, in the presence of SPT.